Psychometric-based domestic violence instruments as an assessment in experiential family counseling - Rima Pratiwi Fadli; A. Muri Yusuf; Firman Firman (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
Domestic abuse is a topic that is often discussed in the community. Experiential family counseling can be used to deal with domestic abuse. In terms of handling, it is vital to undertake a customer assessment. Standard domestic violance instruments that can be utilized in experiential family counseling have not been discovered as a result of library study. As a result, psychometric-based domestic violence tools are required. The creation of psychometric-based instruments results in instruments with high validity and reliability, such as test kits. The Delphi method, focus group discussion, factor analysis, and analysis of standard error of measurement were all used. According to the findings of the study, the application of this psychometric-based instrument has strong discriminating validity and no cross-loading, indicating good convergent validity. In terms of dependability, it also develops devices with a high level of dependability. So that psychometric analysis for evaluation in experiential family therapy can be used to build this instrument of domestic violance.